Effect of CO(2) on Colony Development by Bifidobacterium Species - Kawasaki, Shinji (American Society for Microbiology (ASM), 2007)
This report investigates the requirement for CO(2) for colony formation by Bifidobacterium species in both anoxic and oxic environments. All tested Bifidobacterium species exhibited difficulty in developing colonies in an atmosphere of 100% N(2) but developed well when 1% CO(2) was present. In the presence of CO(2), the oxygen tolerance of the tested species was not improved. In the absence of CO(2), only B. boum, a microaerophilic species, could develop colonies under an N(2)-based 5% O(2) atmosphere, indicating that while CO(2) is not an essential factor for colony development, both CO(2) and O(2) have stimulatory effects on B. boum colony development.